Peran Analisis Dampak Mengenai Lingkungan dalam Mewujudkan Tujuan Sustainable Development Goals (SDGs) - Ega Saputra; Nida Annisa; Muhammad Rizky; Cahya Darmawan (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Rapid infrastructure development in Indonesia poses significant environmental risks, necessitating effective control instruments like the Environmental Impact Assessment (AMDAL). This study analyzes the strategic role of AMDAL in supporting the achievement of Sustainable Development Goals (SDGs), particularly regarding water security, sustainable cities, climate action, and ecosystem conservation. Using a qualitative method with a literature review approach, this research evaluates regulations and academic sources from 2020 to 2025. The findings reveal that AMDAL serves as a critical preventive tool that aligns industrial activities with SDG 6, SDG 11, SDG 13, SDG 14, and SDG 15 through the internalization of ecological costs and strict mitigation hierarchies. Furthermore, AMDAL functions as an essential baseline data source for government monitoring. However, the study identifies substantial barriers to implementation, including a deficit in meaningful public participation, weak law enforcement that renders AMDAL a mere administrative formality, and regulatory dynamics post-Job Creation Law (UUCK) which shifted to a risk-based approach. The study concludes that while AMDAL is theoretically robust as a safeguard for sustainability, its practical implementation requires strengthening in transparency and supervision to effectively bridge economic interests with ecological preservation.